Wellbeing, Values and Lifestyles Towards a New Development Paradigm - Chaturvedi, Sachin; Prabhu, K. Seeta; Saha, Sabyasachi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book with contributions by leading global experts from diverse specialization defines a new development paradigm built on Lifestyle for Environment (LiFE). The volume outlines the contours of LiFE across five facets namely ethics and value system; sustainable consumption and production; modalities of systemic transformation; financing for resilient infrastructure, cities and societies; and wellbeing measurement going beyond GDP. The book prepared as part of the Think 20 (T20) India Task Force 3 on (3z(BLiFE, Resilience and Values for Wellbeing(3y (Bpresents deep insights on socio-economic transformation and ecological balance from a multi-disciplinary perspective. It highlights the importance of normative frameworks in economic thinking, equitable access to finance and technology, role of social enterprises, and imperatives for measuring wellbeing. The book is a must-have resource for political leadership, legislators, policy makers, diplomats, and international organizations in addition to the academic community.s
Lifestyle and Values through the prism of Ancient Indian Tradition -- One Earth, One Family, One Future: Unpacking the theme of India$1 (Bs G20 Presidency, and its Wide-Ranging Implications -- Perspectives on Ethical Values for Lifestyle for Environment (LiFE) Mediated Economy -- Moralising International Relations.s
Keywords: Power resources; Environmental economics; Development economics; Economic policy; Social policy; Industrial policy; Energy policy; Energy and state; Resource and Environmental Economics; Development Economics; Socio-Economic Policy; Regulation and Industrial Policy; Energy Policy, Economics and Management